2010
DOI: 10.1152/japplphysiol.00333.2010
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific lung remodeling and inflammation changes in experimental allergic asthma

Abstract: There is evidence that sex and sex hormones influence the severity of asthma. Airway and lung parenchyma remodeling and the relationship of ultrastructural changes to airway responsiveness and inflammation in male, female, and oophorectomized mice (OVX) were analyzed in experimental chronic allergic asthma. Seventy-two BALB/c mice were randomly divided into three groups (n=24/each): male, female, and OVX mice, whose ovaries were removed 7 days before the start of sensitization. Each group was further randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 40 publications
4
29
2
1
Order By: Relevance
“…In the current study, airway remodeling, as indicated with collagen buildup, was evident 3 months after completion of asthma symptom exposures. These results suggest that some aspects of lung function (inflammation, mucus, gene expression) persist for a long time after allergen exposure, while aspects related to lung structure (collagen build-up) require a longer time to fully form (Tanaka et al, 2002; Antunes et al, 2010; Salmond et al, 2012). …”
Section: Discussionmentioning
confidence: 96%
“…In the current study, airway remodeling, as indicated with collagen buildup, was evident 3 months after completion of asthma symptom exposures. These results suggest that some aspects of lung function (inflammation, mucus, gene expression) persist for a long time after allergen exposure, while aspects related to lung structure (collagen build-up) require a longer time to fully form (Tanaka et al, 2002; Antunes et al, 2010; Salmond et al, 2012). …”
Section: Discussionmentioning
confidence: 96%
“…Genetic association studies of have implicated sex specific effects in INFG [19], TSLP and asthma [26] and CTLA4 with allergic response [27]. Gene expression studies also implicate sex interactions in placental global gene expression in response to asthma [28], IL17BR in allergic response [29] and overall gene expression in humans [30], as well as for asthma related genes in mice [6, 7, 31]. Collectively, these data support a role of sex interaction in the genomics of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Young boys are nearly twice as likely to develop asthma as young girls [3, 4]. Animal models also support sex differences in asthma risk with male mice having greater airway hyperresponsiveness than female mice [5] and female mice having higher levels of airway inflammation and pulmonary remodeling than male mice [6, 7]. …”
Section: Introductionmentioning
confidence: 99%
“…The volume fraction of collapsed and the normal pulmonary areas, magnitude of bronchoconstriction, and number of mononuclear and polymorphonuclear cells in pulmonary tissue were determined by the point-counting technique [18, 19] across 10 random, noncoincident microscopic fields [14, 20, 21]. Collagen fibers (Picrosirius polarization method) were quantified in airways and alveolar septa using Image-Pro Plus 6.0 software [13, 22]. …”
Section: Methodsmentioning
confidence: 99%